Talus fabric, clast morphology, and botanical Indicators of Slope Processes on the Chaos Crags (California Cascades), U.S.A. - Pérez, Francisco (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1998)
Abstract The Chaos Crags, a group of dacite domes in the Cascades Mtns (California), were affected by volcanic debris avalanches ca. 1675 A.D.; these left a sizable deposit and a scar on the north mountain flank, now covered by talus. This report examines the fabric and morphology of talus debris, their spatial variation, and the geomorphic processes presently affecting the slope. The talus presents a bi-segmented profile with a steep upper rectilinear segment and a shorter concave, basal zone. Debris are sorted by size both along (larger clasts downslope) and across the talus (larger particles below the cliffs). Shape sorting is weaker, but clast sphericity increases, and elongation decreases, toward the footslope. Upper-talus fabrics (long axes parallel to talus plane and slope) show that clasts there move by sliding, while basal blocks are deposited by rockfall, which causes more iso- tropic fabrics. Field observations and botanical evidence indicate the overall significance of grain flows, which are prevalent duetoanabundantsupplyofrubbleonthe upper talus. Comparison with similar recent slopes and repeat photography suggest the Chaos talus formed swiftly following dome collapse, when much debris may have collected below the unstable rockwalls. The talus has experienced only modest sedimentation during the 20 th century, and is currently affected by 'normal' mass-wasting processes, which also include snow avalanches and debris flows.